The Impact of Guided-Discovery-Learning Model on Students' Conceptual Understanding and Critical Thinking Skills - Muhali, Muhali; Prahani, Binar Kurnia; Mubarok, Husni; Kurnia, Nova; Asy’ari, Muhammad (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
The current study describes how the guided-discovery-learning model impacts students' conceptual understanding (SCU) and students’ critical thinking skills (SCTS) on the topic of solubility. The quasi-experimental research with a posttest-only nonequivalent control group design was used in this study. The experimental group (45 students) and the control group (47 students) were selected by the saturated sampling technique. Data on SCU was collected using an objective true false test instrument with correction/proofing, while data on critical thinking skills was collected using an essay test instrument. The research data were analyzed descriptively and statistically (Mann-Whitney U). The research found the SCU (mean= 81.51 vs. mean= 72.81) and SCTS (mean= 70.46 vs. mean= 58.43) in the experimental group was better than the control group, both descriptively and statistically (p < 0.05). These findings indicate that the guided-discovery-learning model significantly impacted SCU and SCTS on the solubility topic.